Vinyl sulfone functionalized injectable thermogels for facile peptide coupling - Oei, John Xin Jian (Nanyang Technological University, 2024)
Thermogels are amphiphilic polymers that can undergo temperature dependent sol-gel transitions due to the formation of supramolecular interactions. Those synthesized by Loh et al. have high water content and experience gelation at physiological temperature, making them uniquely suited for the delivery of encapsulated cells. However, they lack cell adhesion moieties necessary for long term cell survival. Divinyl sulfone (DVS) is a promising candidate to link the polymer and an adhesion ligand containing the thiol bearing peptide cysteine via thiol-Michael addition due its efficiency and mild reaction conditions. Thus, this project determined a method of functionalising the thermogel with DVS. Two different methods were tested, one using NaOH as a catalyst in aqueous conditions, and the other using 4-Dimethylaminopyridine (DMAP) as a catalyst in an organic solvent. The former method was chosen for the thermogel, due to the DMAP catalyzed reaction producing unwanted chemical cross-links. Rheological measurements of the DVS conjugated thermogel revealed a lowered gelation temperature, potentially increasing the biocompatibility by decreasing the polymer loading needed for gel formation. Lastly, the thiol bonding ability was demonstrated by conjugating a model thiol containing peptide to the DVS incorporated thermogel. Future studies, such as bioactive peptide functionalization and formation of a strong crosslinked gel in situ are next planned for the DVS functionalized thermogel.